2016
DOI: 10.1093/mnras/stw2303
|View full text |Cite
|
Sign up to set email alerts
|

Accretion at the periastron passage of Eta Carinae

Abstract: We present high resolution numerical simulations of the colliding wind system η Carinae, showing accretion onto the secondary star close to periastron passage. Our hydrodynamical simulations include self gravity and radiative cooling. The smooth stellar winds collide and develop instabilities, mainly the non-linear thin shell instability, and form filaments and clumps. We find that a few days before periastron passage the dense filaments and clumps flow towards the secondary as a result of its gravitational at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The code includes radiative cooling based on Sutherland & Dopita (1993) and a prescription that describes the accretion. The details regarding the modifications and enhancements we did to the code are described in Kashi (2017) and Kashi (2019). The two stars are treated as solid spheres.…”
Section: The Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The code includes radiative cooling based on Sutherland & Dopita (1993) and a prescription that describes the accretion. The details regarding the modifications and enhancements we did to the code are described in Kashi (2017) and Kashi (2019). The two stars are treated as solid spheres.…”
Section: The Numerical Simulationmentioning
confidence: 99%
“…However, η obtains higher values close to periastron passage, where, as mentioned, the secondary wind does not reach its terminal velocity. As Nazé et al (2017) found that the wind collision in HD 166734 is non-adiabatic, we include radiative cooling, according to the method described in Kashi (2017). As we discuss below, the cooling leads to instabilities in the colliding winds structure (see section 3).…”
Section: The Numerical Simulationmentioning
confidence: 99%
“…These steps are rarely explored in inspiral simulations due to the computational difficulties, although some results have shown that less evolved giants merge more easily (24). Material may also form a disc around the two cores that could drive the last merging steps (25).…”
mentioning
confidence: 99%
“…An important parameter we studied is the mass loss rate of the primary, for which we used values within the range explored in the literature (see Kashi 2017). We demonstrated that the mass loss rate of the primary affects the accretion rate of the secondary in nonlinear way, and found strong dependency between the accreted mass and the mass loss rate of the primary.…”
Section: Simulations Resultsmentioning
confidence: 96%
“…The final evidence for accretion came from the simulations of Kashi (2017), that showed the destruction of the colliding winds structure into filaments and clumps that later were accreted onto the secondary. Kashi (2017) demonstrated that dense clumps are crucial to the onset of the accretion process. The clumps were formed by the smooth colliding stellar winds that developed instabilities that later grew into clumps (no artificial clumps were seeded).…”
mentioning
confidence: 99%